Sosialisasi Bijak dalam Menggunakan Gadget untuk Siswa SMP Bustanul Ulum NU 02 Bumiayu - Nur Izzir Rohman, Ahmad; Khoerotunnisa, Ana; Edi Laksono, Gangsar; Muchamad Masykur , Zein (Jurnal Cahaya Edukasi, 2025)
The use of gadgets among students is increasing, bringing both positive and negative impacts on their lives. This study aims to provide education to students of SMP Bustanul Ulum NU 02 Bumiayu about the wise use of gadgets in order to minimize their negative impacts. The methods used in this activity are lecture-based socialization, interactive discussions, and questions and answers. This activity was carried out on July 24, 2024 and involved students in educational sessions regarding the positive and negative impacts of gadget use, as well as strategies for managing their use in a healthier way. The results of the socialization showed that students began to understand the risks of gadget dependence, sleep disorders due to exposure to blue light, and other social and psychological impacts. Through active discussions and interactions, students were also able to identify solutions, such as limiting the time spent using gadgets, avoiding use before bed, and prioritizing interactions in the real world. Analysis of this activity shows that an educational approach based on direct interaction can increase students' awareness of more responsible gadget use